Ecranization of Novel Azzamine Adapted into a Film Azzamine Directed by Benni Setiawan - Nur R. Male; Salam (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe: 1) the ecranization of Sophie Aulia's novel Azzamine into the film Azzamine directed by Benni Setiawan on the elements of characters and characterization, plot, and setting reviewed from the aspect of reduction; 2) the ecranization of Sophie Aulia's novel Azzamine into the film Azzamine directed by Benni Setiawan on the elements of characters and characterization, plot, and setting reviewed from the aspect of addition; 3) the ecranization of Sophie Aulia's novel Azzamine into the film Azzamine directed by Benni Setiawan on the elements of characters and characterization, plot, and setting reviewed from the aspect of variation changes. The research instrument is a researcher or human instrument. The data of the ecranization of the novel into the film were analyzed using the theory of ecranization. The results of the ecranization of Sophie Aulia's novel Azzamine into the film Azzamine directed by Benni Setiawan: 1) There are 14 changes in the elements of character and characterization, 3 changes in the plot element in the middle stage of the climax and the final stage, and 3 changes in the setting element. (2) There are 5 additions in the elements of character and characterization, 5 additions in the plot element in the three stages of the introduction, middle stage, and final stage, and 3 additions in the setting element. (3) There are 3 changes in the elements of character and characterization, 2 changes in the plot element in the introduction stage and the middle stage of the complication, and 5 changes in the setting element.